Worries about labor and birth: a population-based study of outcomes for young primiparous women - Henderson, J; Redshaw, M (Wiley, 2016)
Background Pregnancy at a young age is a continuing public health concern strongly associated with socioeconomic deprivation, social isolation, and stigma. The objectives were to see whether, compared with women aged 21 or more, women aged 20 years or younger worried more about labor and birth, and had poorer maternal outcomes. Another objective was to investigate the extent to which worries about labor and birth mediated the associations between young age and outcomes.